Health promotion models to improve quality of life type 2 diabetes mellitus sufferers - Samingan, Samingan; Mudigdo, Ambar; Sulaiman, Endang Sutisna; Lestari, Eny (Edelweiss Applied Science and Technology, 2025)
Health Promotion Model to Improve the Quality of Life of Type 2 Diabetes Mellitus Patients is a study that aims to improve the quality of life of type 2 diabetes mellitus patients through health promotion. This study uses a quantitative research method with a descriptive analytical research type and a cross-sectional research design. This study was conducted in Bekasi City, West Java Province, with a population of type 2 DM adults aged > 26 years who live in Bekasi City. Based on the health profile of the Bekasi City Service in 2020, there was a prevalence of type 2 DM of 57,029 people from 12 sub-districts in Bekasi City, with a sample of 269 respondents. From the results of the descriptive statistical analysis, it can be concluded that the respondents have an average age of 55 years with quite large variations. Respondent Knowledge is relatively high with an average score of 8.6799. Respondent income varies greatly with an average of IDR 4,723,395.6552000000. Scores on health promotion models, action triggers, community change strategies, self-empowerment, and quality of life varied considerably.